1992
DOI: 10.1242/jcs.102.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Structural and histochemical studies of Golgi complex differentiation in salivary gland cells during Drosophila development

Abstract: Morphological alterations in the Golgi complex (GC) and changes in the distribution of acid phosphatase (AcPase), thiamine pyrophosphatase (TPPase), complex carbohydrates and reduced osmium tetroxide compounds in this organelle were studied in the salivary gland cells of Drosophila during larval and prepupal development. The morphology and the AcPase, TPPase and complex carbohydrates cytochemical patterns of the Golgi complex varied characteristically during cell differentiation. At the early 3rd instar period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…It was recently demonstrated that many proteins functioning in the endolysosomal pathway are required for secretory granule maturation in the Drosophila salivary gland [ 8 10 ], a process possibly similar to the biogenesis of lysosome-related organelles [ 9 ]. Acid phosphatase activity was detected in immature secretory granules, suggesting that this enzyme is required for processing of secretory proteins [ 11 ]. Secretory granules can fuse with lysosomes, which regulates the glue granule pool by selective degradation (crinophagy) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that many proteins functioning in the endolysosomal pathway are required for secretory granule maturation in the Drosophila salivary gland [ 8 10 ], a process possibly similar to the biogenesis of lysosome-related organelles [ 9 ]. Acid phosphatase activity was detected in immature secretory granules, suggesting that this enzyme is required for processing of secretory proteins [ 11 ]. Secretory granules can fuse with lysosomes, which regulates the glue granule pool by selective degradation (crinophagy) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%